Continuous flow isotope ratio mass spectrometry of carbon dioxide trapped as strontium carbonate - Paul, Eldor A., author; Porter, L. K., author; Harris, D., author; Marcel Dekker, Inc., publisher (Colorado State University. Libraries, 1997)
The isotopic signal provided by differential discrimination against atmospheric carbon dioxide (13CO2) by C3 and C4 plant photosynthetic pathways is being widely used to study the processes of carbon (C) fixation, soil organic matter formation, and mineralization in nature. These studies have been facilitated by the availability of automated C and nitrogen (N) combustion analyzers (ANCA) combined with continuous flow isotope ratio mass spectrometers (CFIRMS). Analysis of 13CO2 in these instruments requires consistent sample mass for best precision, a requirement that is easily satisfied for soil and tissue samples by adjusting sample weight. Consistent CO2 sample size is much more difficult to achieve using gas handling systems for samples of headspace gases when CO2 concentrations vary widely. Long storage of gaseous samples also is difficult. Extended respiration studies are most easily conducted by trapping CO2 in alkali and conversion to an insoluble carbonate. Thermal decomposition of the carbonate in an on-line ANCA allows consistent and optimal CO2 sample mass to be obtained. The use of precipitated carbonates also facilitates storage of samples and enables full automation of sample analysis using an ANCA interfaced to a CFIRMS. Calcium (Ca), strontium (Sr), and barium (Ba) carbonates were tested. Strontium carbonate (SrCO3) with the addition of vanadium pentoxide (V2O5) as a combustion catalyst was found most suitable.
Keywords: photosynthesis; pathways; C4; C3; 13CO2; plant biomass; isotopic signal